Evaluation of Genetic Diversity of Wan Khanmak Herb Using AFLP Marker - Sirisak Soonthornyatara (Science Faculty of Chiang Mai University, 2020)
Wan Khanmak is a common name of Thai herb which is widely used as longevity enhancer. This medicinal species was previously classified as Aglaonema simplex (Blume) Blume. This experiment aims at collecting Wan Khanmak germplasms and evaluating the genetic diversity of this herb using DNA marker. The Amplified fragment length polymorphism (AFLP) technique was used to generate DNA fingerprint of Wan Khanmak samples which were collected throughout Thailand. When considering both DNA fingerprint data and morphological information, it revealed that a total of 115 Wan Khanmak accessions could be divided into seven major clusters. Cluster I consisted of 91 samples which were classified as Aglaonema simplex (Blume) Blume. The cluster II-VII were assigned to six species; Aglaonema sp. (1), Aglaonema modestum Schott ex Engl., Aglaonema cochinchinense Engl., Aglaonema ovatum Engl., Aglaonema sp. (2) and Aglaonema nitidum (Jack) Kunth, respectively. Genetic similarity between samples were calculated and the results ranged from 0.24-1.00 with an average of 0.627. The average of genetic similarity coefficient of A. simplex Bl. samples in cluster I was about 0.808, indicating that this species has low to moderate level of genetic variation. The A. simplex Bl. could be further divided into 12 subgroups. This experiment also indicated that there were other Aglaonema species that were misused as A. simplex Bl., because some Aglaonema spp. have similarities in general morphology and growth habitat.